HUBUNGAN TINGKAT KECEMASAN DENGAN ADAPTASI SOSIAL PADA LANSIA DENGAN PENDEKATAN TEORI MODEL ADAPTASI ROY DI UPT PSTW BONDOWOSO - Marroh, Ilza Sulsilatul; Hafifah, Vivin Nur; Khotimah, Husnul (NHM PRESS, 2025)
Introduction: The elderly or elderly are often understood by health and social practitioners as a vulnerable group with the increasing number of elderly population, there are also several problems that will arise, including physical or psychosocial problems. One of the psychosoial problems often experienced by the elderly is anxiety or anxiety. One of the most common causes of anxiety in the elderly is social support, especially in the elderly who are in social institutions.Researchers' objective: to determine the relationship between anxiety levels and social adaptation in the elderly with roy's adaptation model theory approach at UPT PSTW Bondowoso. Research Method: using a type of quantitative research in the form of correlation research that essentially examines the relationship between variables. In this study, there were 80 respondents who were UPT PSTW Bondowoso The instrument used in this study was a questionnaire consisting of 14 questions and 14 questions. Results: this study used spearmen't rank test, P value of 0.000. Because of the P<0.05 value, Ho was rejected and Ha was accepted so that it can be concluded that there is a fairly high positive relationship between the relationship between the level of anxiety and social adaptation in the elderly with the approach of roy's adaptation model theory at UPT PSTW Bondowoso. Conclusion: based on the results of this study, there is a relationship between anxiety levels and social adaptation in the elderly with roy's adaptation model theory approach at UPT PSTW Bondowoso.